The Effect of Production and Sales on Leverage and Profitability in The JKN Era (State-Owned and Private Pharmaceutical Companies Tbk, Period 2014–2018) - Pratista Hangline Herlistiana; MGS. Aritonang; Tedy Herdiana (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The implementation of the National Health Insurance (JKN) by BPJS has an impact on the pharmaceutical industry, there are an increase in demand for generic drugs, resulting in increased production, increased drug consumption in quantity, but decreased sales because pharmaceutical companies have to compete with small margins. The purpose of this study is to describe the financial performance of pharmaceutical companies in the JKN era, to analyze the factors that can affect leverage and profitability. This research was conducted at state-owned pharmaceutical companies (PT. Kimia Farma and PT. Indofarma) and private pharmaceutical companies (PT Merck and PT Kalbe). The two independent variables in this study, namely production and sales, were analyzed to see how they affect the leverage and profitability dependent variables. Descriptive analysis shows the financial performance of each company in the JKN era. Product analysis shows that at PT Kimia Farma production has a strong correlation with leverage and sales growth has a strong correlation with profitability, at PT Indofarma production and sales growth has a strong correlation with leverage and profitability, at PT Merck leverage has a strong correlation with profitability, while the correlation between sales growth on leverage does not show a strong correlation with the four companies, at PT Kalbe sales growth has a strong influence on leverage and leverage has a strong effect on profitability